New Names for Old Tumors: The Impact of Reclassifying "Clear Cell" Hepatocellular Carcinomas Using Current Terminology. Issue 5 (1st December 2020) - Wong, Mary; Waters, Kevin M; Guindi, Maha; Larson, Brent K
Abstract: Objectives: Previous studies described "clear cell" hepatocellular carcinoma (HCC), although definitions have varied. New clear cell subtypes of HCC have been proposed, including chromophobe (C-HCC), steatohepatitic (SH-HCC), and steatotic (S-HCC), and this study assessed the utility and clinical-pathologic profile of these subtypes. Methods: Current histologic definitions, including 3 separate proposed definitions for SH-HCC, were applied to tumors previously characterized as clear cell HCC. Histologic and clinical variables were analyzed. Results: Of 66 HCCs, 51 (77%) were classified using modern definitions, including 34 SH-HCCs, 15 S-HCCs, and 2 C-HCCs. Compared with the most permissive SH-HCC definition, the other 2 definitions designated 30 and 25 SH-HCCs (−12% and −26% cases, respectively). Unsurprisingly, S-HCC and SH-HCC were associated with steatotic clear cells ( P < .0001). S-HCC was also more typically early type and low grade ( P = .0017). The remaining unclassified clear cell HCCs were associated with flocculent (rather than steatotic or optically clear) cytoplasm ( P < .0001) but otherwise demonstrated no discrete clinical-pathologic profile. Conclusions: Current definitions could be used to reclassify the majority of "clear cell" HCCs. The subtypes are significantly correlated with a few variables, suggesting valid differences of the subtypes, although additional study is warranted, particularly to standardize the definition of SH-HCC.